After that night - Slaughter, Karin, 1971- (Slaughter, Karin, 1971- Will Trent series., 2023)
Fifteen years ago, Sara Linton's life changed forever when a celebratory night out ended in a violent attack that tore her world apart. Since then, Sara has remade her life. A successful doctor, engaged to a man she loves, she has finally managed to leave the past behind her. Until one evening, on call in the ER, everything changes. Sara battles to save a broken young woman who's been brutally attacked. But as the investigation progresses, led by GBI Special Agent Will Trent, it becomes clear that Dani Cooper's assault is uncannily linked to Sara's. And it seems the past isn't going to stay buried forever.